2009
DOI: 10.1073/pnas.0905364106
|View full text |Cite
|
Sign up to set email alerts
|

GPR17 is a negative regulator of the cysteinyl leukotriene 1 receptor response to leukotriene D 4

Abstract: The cysteinyl leukotrienes (cys-LTs) are proinflammatory lipid mediators acting on the type 1 cys-LT receptor (CysLT 1R) to mediate smooth muscle constriction and vascular permeability. GPR17, a G protein-coupled orphan receptor with homology to the P2Y and cys-LT receptors, failed to mediate calcium flux in response to leukotriene (LT) D 4 with stable transfectants. However, in stable cotransfections of 6؋His-tagged GPR17 with Myc-tagged CysLT 1R, the robust CysLT 1R-mediated calcium response to LTD4 was abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
112
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 43 publications
(57 reference statements)
13
112
2
Order By: Relevance
“…Our data indicate that GPR17 is neither activated nor internalized by these ligands, whereas receptors that are established targets of these ligands demonstrate robust activation and internalization. Moreover, our data are consistent with GPR17 acting as a negative regulator of CysLTR1 as reported previously (Maekawa et al, 2009). …”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our data indicate that GPR17 is neither activated nor internalized by these ligands, whereas receptors that are established targets of these ligands demonstrate robust activation and internalization. Moreover, our data are consistent with GPR17 acting as a negative regulator of CysLTR1 as reported previously (Maekawa et al, 2009). …”
Section: Introductionsupporting
confidence: 81%
“…The orphan GPCR GPR17 was reported to be activated by uracil nucleotides (UDP), nucleotide sugars (UDP-glucose and UDP-galactose), and cysteinyl leukotrienes (LTC4 and leukotriene D4), and coupled to both inhibition of cAMP accumulation and intracellular Ca 21 mobilization (Ciana et al, 2006;Pugliese et al, 2009), although other studies have reported different agonist selectivity (Benned-Jensen and Rosenkilde, 2010) or no activation of GPR17 by these ligands (Heise et al, 2000;Maekawa et al, 2009). To investigate whether these compounds were agonists at GPR17, HA-tagged GPR17 was stably expressed in C6 and CHO cells by retroviral infection, and its capacity to promote inhibition of cAMP accumulation was assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, GPR17 was identified as a negative regulator of the Cys-LT1R suppressing CysLT1R-mediated function at the cell membrane. 12 Because of these contradictory results, the activation of GPR17 by nucleotides and cysteinyl-leukotrienes is still a subject of intense discussion and controversy.Recently Hennen et al 5 identified 2-carboxy-4,6-dichloro-1H-indole-3-propionic acid (1, MDL29,951) and 3-[(E)-3-(anilino)-3-oxoprop-1-enyl]-4,6-dichloro-1H-indole-2-carboxylic acid (GV150526A, gavestinel, 2) as synthetic, small molecule GPR17 agonists and characterized them in different functional assays including G q -mediated intracellular calcium mobilization, G i -coupled inhibition of adenylate cyclase (AC), G s -coupled stimulation of AC, and dynamic mass redistribution (Figure 1). Activation of GPR17 by 1 was demonstrated in multiple cell types including recombinant cells as well as primary rat oligodendrocytes.…”
mentioning
confidence: 99%
“…Accordingly, mice deficient in 5-LOX, FLAP, or LTC 4 synthase are all highly resistant to asthmatic challenge [14,31], and an antagonist of CysLT1 is now clinically used as an anti-asthmatic drug worldwide. in addition, it has been recently shown that CysLT1 and CysLT2 can form a heterodimer, that GPr17 counteracts the CysLT1 signaling, and that P2Y12, a purinergic GPCr, is important for the biological action of LTE 4 , the most stable and abundant cys-LT in biological fluid [43,62]. The first LTB 4 receptor, BLT1, is a fundamental T H1 and T H2 immune regulator which acts through recruitment of T lymphocytes [80].…”
Section: Class 1: Eicosanoidsmentioning
confidence: 99%